Фармакоэпидемиологический и фармакоэкономический анализ эффективности применения препаратов кальция в лечении остеопении у больных с бронхиальной астмой - А. Л. Хохлов; А. Е. Мирошников; Л. И. Лаврентьева (SINAPS LLC, 2012)
In the light of bronchial asthma (BA) incidence rise in Russia and in the world, study of the frequency of osteopenia and methods of correction of bone mass reduction in patients with BA is very important. We have conducted a comprehensive analysis of the problem of osteopenia in patients with BA, calculated indicators of awareness of physicians and patients about this problem and the frequency of osteopenia. A comparative clinical and economic research was realized in which course it was found out, that Natecal D3 (Italfarmaco) is characterized by a good profile of the portability and security, leads to an increase in bone mass even during the 6-month period of treatment, and the № 60 form is especially beneficial from the economic point of view.